Perilaku Hidup Bersih dan Sehat melalui Upaya Pemberdayaan Masyarakat - Imelda Fitri; Rifa Rahmi; Hotmauli Hotmauli (Universitas Faletehan, 2021)
The data of Clean and Healthy Living Behavior (CHLB) in Riau Province in the last three years was always the lowest. The purpose of this study was to examine the influence of family-based community empowerment through integrated healthcare center (Ina. posyandu), the caders, the organizing or group on the CLHB at Muara Fajar Landfills, Rumbai, Pekanbaru. The research design was cross sectional. The samples were 26 housewives at RT 01/RW 03 of Muara Fajar Landfills, Rumbai, Pekanbaru. The research instrument was a questionaire. The data was analyzed by Pearson correlation and linier regression test. The results showed that family-based community empowerment through caders significantly influenced the clean and healthy living behavior (p value 0.0020) and had the biggest influence 0.2 times (r = 0.455; R2= 0.207). The scores was compared to the family-based community empowerment through integrated health care center and the organizing which influence scores respectively were 0.123 times (r = 0.348; R2= 0.121) and 0.024 times (r = 0.141; R2= 0.020). There were still community on health standard I (3.9%) and and health standard II (7.7%).